CONCEPTUAL ASPECTS AND THE MOST USED PRACTICES IN OBTAINING THE RELIABILITY OF ENTITY VALUE ESTIMATION - BIRCA, Iulita; TIRLEA, Mariana Rodica; GANEA, Victoria; BUZU, Olga (Economy and Sociology, 2021)
Estimating the entity value is topical and of particular interest to managers and business owners, who in turn hope that through the evaluation they will obtain parallel and new possibilities for the business remediation. In this context, managers seek the support of qualified assessors, who will conduct a thorough analysis of the entity’s state at a given date, will apply the most effective evaluation methods. In this paper we proposed to investigate and analyze the theoretical aspects of the entity value estimation (EVE), rendered in the opinion of the well-informed researchers and in the light of the evaluation standards. As a result, we note that the criteria of evaluations have been supplemented with the following criterion: by type of activity of the economic entity. We estimate the evaluation methods in order to identify the most accepted and effective method for this important process to the entity. For the practical aspect of the investigation, we focused on the method of comparison in the market valuation of the enterprise, in order to establish the statistical indicators consisting of the calculation of the median and the arithmetic mean. Based on the calculations made in the practical part, we have found that an economic entity can change its own value, in particular, by the way its values are profitable. In estimating the value of the entity, a decision-making function is attributed to the rests with the assessor, in particular with regard to the methods selected and applied professionally by the entity, in compliance with professional valuation standards and current regulations, as the fair estimation of the entity’s value leads to a secure future and a guaranteed success.